2008
DOI: 10.1177/154405910808700814
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use and Post-operative Bleeding from Dental Extractions

Abstract: Aspirin is a common, chronically administered preventive treatment for cardiovascular disease, but is often discontinued prior to invasive dental procedures because of concern for bleeding complications. We hypothesized that aspirin does not cause increased bleeding following a single tooth extraction. Thirty-six healthy persons requiring a tooth extraction were randomized to receive 325 mg/day aspirin or placebo for 4 days. Cutaneous bleeding time (BT) and platelet aggregation tests were obtained prior to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 33 publications
1
25
1
5
Order By: Relevance
“…Pour l'ensemble de ces études cliniques [24,36,48,50,54,56,113,185,197,204,228,234,248,281], aucune complication hémorragique sévère non contrôlable par des mesures d'hémostase locale n'est rapportée. Deux études [212,237] ont évalué la perte sanguine après extraction dentaire chez des patients sous aspirine ou clopidogrel comparativement à des patients ne prenant pas d'aspirine ou ayant interrompu leur traitement par AAP 7 jours avant la procédure dentaire ou sous AINS.…”
Section: Arrêt Ou Maintien Du Traitement Par Agent Antiplaquettaire ?unclassified
See 1 more Smart Citation
“…Pour l'ensemble de ces études cliniques [24,36,48,50,54,56,113,185,197,204,228,234,248,281], aucune complication hémorragique sévère non contrôlable par des mesures d'hémostase locale n'est rapportée. Deux études [212,237] ont évalué la perte sanguine après extraction dentaire chez des patients sous aspirine ou clopidogrel comparativement à des patients ne prenant pas d'aspirine ou ayant interrompu leur traitement par AAP 7 jours avant la procédure dentaire ou sous AINS.…”
Section: Arrêt Ou Maintien Du Traitement Par Agent Antiplaquettaire ?unclassified
“…• En cas d'extraction simple (unitaire et multiple), les mesures d'hémostase conventionnelles (sutures + compression mécanique de 30 minutes) sont efficaces et suffisantes pour contrôler le saignement postopératoire chez les patients sous aspirine [24,50,185,204,281] ou sous clopidogrel [54,197] avec un taux de saignement postopératoire rési-duel acceptable d'environ 2 à 3 %. Sous bithérapie aspirine + clopidogrel, une hémostase locale associant sutures + compression semble insuffisante [197] [54,197,227].…”
Section: Quelle Hémostase Locale Doit-on Réaliser Pour Contrô-ler Lunclassified
“…Local measures are sufficient to control any bleeding during surgery. Brennan et al [2] also conducted a study on 36 patients on aspirin, and found and suggested that there is no indication for discontinuing aspirin for individuals requiring a single-tooth extraction, or similarly invasive dental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Nos dias atuais, há um aumento no número de pessoas portadoras de cardiopatias, não apenas pelo fato do diagnóstico precoce e/ou aumento da sobrevida da população, mas também pelo crescente aumento dos fatores de risco cardiovascular, como sedentarismo, tabagismo, hipertensão, dislipidemia, diabetes Durante algum tempo as pesquisas clínicas se ocuparam de comprovar e assegurar ao cirurgião dentista clínico que a utilização de AAS não configura um risco de hemorragias incontroláveis durante procedimentos odontológicos invasivos (Medeiros et al, 2011 A situação ideal, ao submeter um paciente sob terapia antiplaquetária dual a um procedimento odontológico invasivo, seria, teoricamente, contar com exames de agregação plaquetária, para poder avaliar o risco de hemorragia transoperatória e recomendar, se necessário, tratamento em nível hospitalar (Brennan et al, 2008;Morimoto et al, 2009;Morimoto et al, 2011;Fakhri et al, 2013 McKay et al, 2004, Zhou;Schmaier, 2005, Neunert;Journeycake, 2007, Rezende et al, 2010.…”
Section: Discussionunclassified
“…Por outro lado, (Brennan et al, 2008;Minematsu, 2009;Morimoto et al, 2011;Fakhri et al, 2013) (Grines et al, 2007). Isto faz com que muitos profissionais recomendem a suspensão da medicação antes de qualquer procedimento cirúrgico odontológico, entretanto, a suspensão desta terapia expõe os pacientes portadores de stent coronariano à riscos adversos de eventos trombóticos.…”
Section: Introductionunclassified